Pengaruh Metode Talking Stick Berbantuan Media Teka-Teki Silang Terhadap Kemampuan Mengidentifikasi Teks Fabel Pada Siswa Kelas VII SMP Negeri 6 Percut Sei Tuan - Azmi Fadhilah Munthe; Achmad Yuhdi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Students encounter difficulties in learning to understand fable texts. This is evident from their lack of attention during instructional sessions, as most students tend to engage in distractions within the classroom, display difficulty in being managed, and struggle to comprehend the texts when given assignments. The aim of this research is to determine (1) the ability of seventh-grade students of SMP Negeri 6 Percut Sei Tuan in identifying fable texts using the talking stick method; (2) the ability of seventh-grade students of SMP Negeri 6 Percut Sei Tuan in identifying fable texts using the talking stick method aided by crossword puzzle media; (3) the influence of the talking stick method aided by crossword puzzle media on the ability to identify fable texts in seventh-grade students of SMP Negeri 6 Percut Sei Tuan.. This research employs an experimental method with a two-group only post-test control design. The findings of the study reveal that 1) The ability of seventh-grade students of SMP Negeri 6 Percut Sei Tuan in identifying fable texts using the talking stick method falls within the good category, with an average score of 78. 2) The ability of seventh-grade students of SMP Negeri 6 Percut Sei Tuan in identifying fable texts using the talking stick method aided by crossword puzzle media has improved and falls within the excellent category, with an average score of 88.16. Based on the t-test, with a significant level value of α = 0.05 and n = 30, the t-table value obtained is 2.04. Therefore, it can be concluded that the t-value > t-table, which is 3.35 > 2.04. This proves that there is a significant influence of using the talking stick method aided by crossword puzzle media on the ability to identify fable texts in eighth-grade students of SMP Negeri 6 Percut Sei Tuan.